Enhancing Trading Strategies: Mandani Fuzzy Logic Forecasting for Borsa Istanbul Stocks Using Important Indicators - Ozer, Erman; SEVİNÇKAN, Nurullah and DEMİROĞLU, Erdem and AYDOS, Hasan (International Journal of Computational and Experimental Science and Engineering, 2025)
Recent years have seen significant financial market advancements, predicting stock or crypto exchange prices is a complex and risky process. Developments in the financial world are becoming increasingly interesting, especially for traders and investors who want to maximise profits. Nowadays, financial forecasting analysis is changing as conditions change and popular methods are preferred instead of traditional methods. Current changes and developments in the markets have become very important with the fuzzy logic method and the selection of indicators. In this study, contrary to the existing indicators, significant success was achieved with the 6 most popular indicators (RSI, SO, MACD, OBV, BB, CCI). Since each indicator has its pros and cons, these aspects are balanced with the mandani fuzzy logic method. This study provides forecasting analysis with mandani fuzzy logic method to facilitate the operation of 655 companies listed in Borsa Istanbul (BIST). FROTO stock data belonging to Ford Otosan company on BIST is used as data. This study aims to enable traders and investors to maximize their profits or increase their portfolios. The most accurate results were obtained using membership functions created for the indicators and 34 rules created using the Mamdani fuzzy method.